ENGLISH BORROWING IN INDONESIAN LANGUAGE SPOKEN BY INDONESIAN TEENAGERS IN JUNIOR HIGH SCHOOL - Gustara, Restu Anggi (2015)
This study looks specifically at the borrowing words phenomenon among teenagers in one junior high school in Bandung. The borrowing words phenomenon being inverstigated in this study included the types of borrowing words, phonological process, the most dominant part of speech in borrowing words and some possible factors for borrowing to occur. The data were taken from 18 teenagers from three different grades. The seventh grade consists of six teenagers (11-12 years old), eighth grade consists of six teenagers (12-13 years old) and ninth grade consists of six teenagers (13-14 years old). The data were analyzed in a descriptive qualitative method by using the theories from Hoffer (2005), Campbell (1998), Field (2002) and Thomas (1993). The findings showed that the most frequent type of borrowing in all grades is loanword. In terms of phonological processes, the most frequent sound change occurs in the borrowing is Monophthongisation. With regard to parts of speech, noun appears as the dominant part of speech in the borrowing words. Four possible factors that cause borrowing words in teenagers are due to the frequency in using borrowing words, the number of speakers around the respondents, the habitual of expressing the English words and the low competence of the speakers. In conclusion, it seems apparent that borrowing words in this context udergo many phonological adaptations. Keywords: borrowing words, loanword, sound change, factors of borrowing words Abstrak: Penelitian ini meneliti fenomena kata serapan (borrowing) yang terdapat di remaja Sekolah Menengah Pertama. Data untuk penelitian ini diperoleh dari 18 siswa remaja dari tiga kelas yang berbeda. Kelas tujuh terdiri dari enam siswa remaja (berusia 11-12 tahun), kelas delapan terdiri dari enam siswa remaja (12-13 tahun), dan kelas Sembilan terdiri dari enam siswa remaja pula (13-14 tahun). Data tersebut dianalisis dalam kerangka metode deskriptif kualitatif dengan menggunakan teori yang diformulasikan oleh Hoffer (2005), Campbell (1998), Field (2002), dan Thomas (1993). Hasil peneilitian ini menunjukkan bahwa tipe borrowing yang paling sering muncul di semua kelas ialah loanword. Dalam kaitannya dengan proses fonologis, perubahan bunyi (sound change) yang paling sering muncul dalam kata serapan tersebut ialah monopthingisation. Dalam kelas kata, kata benda merupakan kelas kata yang paling dominan dalam kata serapan yang muncul. Kesimpulannya, terlihat jelas bahwa kata serapan mengalami banyak adaptasi fonologis. Kata Kunci: kata serapan, loanword, sound change, faktor kata serapan